Prognostic factors for outcomes of idiopathic sudden sensorineural hearing loss: protocol for the SeaSHeL national prospective cohort study - Helen Blackshaw; Anne GM Schilder; Rishi Mandavia; Gerjon Hannink; Muhammad Nayeem Ahmed; Yaami Premakumar; Timothy Shun Man Chu; Tanjinah Ferdous; Nishchay Mehta; Joseph Manjaly; Maha Khan (BMJ Open)
Introduction The mainstay of treatment for idiopathic sudden sensorineural hearing loss (SSNHL) includes oral steroids, intratympanic steroid injections or a combination of both. The National Institute for Health and Care Excellence, in their recent hearing loss guidelines, highlighted the paucity of evidence assessing the comparative effectiveness of these treatments; and the National Institute for Health Research (NIHR) Health Technology Assessment Programme has since released a commissioned call for a trial to identify the most effective route of administration of steroids as a first-line treatment for idiopathic SSNHL. For such trials to be run effectively, reliable information is needed on patients with SSNHL: where they present, numbers, demographics, treatment pathways, as well as outcomes. This study will collect these data in a nationwide cohort study of patients presenting with SSNHL across 97 National Health Service (NHS) trusts. The study will be delivered through ear, nose and throat (ENT) trainee networks, the NIHR Clinical Research Network (CRN) Audiology Champions and the NIHR CRN. Importantly, this study will also provide a dataset to develop a prognostic model to predict recovery for patients with idiopathic SSNHL. The study objectives are to: (1) map the patient pathway and identify the characteristics of adult patients presenting to NHS ENT and hearing services with SSNHL, (2) develop a prognostic model to predict recovery for patients with idiopathic SSNHL and (3) establish the impact of idiopathic SSNHL on patients’ quality of life (QoL).Methods and analysis Study design: national multicentre prospective cohort study across 97 NHS trusts.Inclusion criteria: adult patients presenting to NHS ENT and hearing services with SSNHL.Outcomes: change in auditory function; change in QoL score.Analysis: multivariable prognostic model, using prespecified candidate predictors. Mean change in QoL scores will be calculated from initial presentation to follow-up.Ethics and dissemination Health Research Authority and NHS Research Ethics Committee approved the study. Publication will be on behalf of study sites and collaborators.Trial registration number ClinicalTrials.gov Registry (NCT04108598).